Can computational thinking be improved by using a methodology based on metaphors and scratch to teach computer programming to children? - Pérez-Marín, Diana; Hijón-Neira, Raquel; Bacelo, Adrián; Pizarro, Celeste (Computers in human behavior, 2020)
Computational thinking (CT) is a key skill in the 21st century. However, it is not clear which is the most effective way to acquire and improve CT. Big research efforts are made to determine which pedagogical means should be used. One research trend is based on the idea that teaching programming since Primary Education suffices to improve CT. In our previous work, we proposed and validated a methodology based on metaphors and used of Scratch (MECOPROG) to teach basic programming concepts to children. It is our hypothesis H that by applying MECOPROG, students will develop their CT. To check H, we carried out an experiment with 132 Primary Education Students (9–12 years in age). At the beginning of the experiment, all students were asked to fill in a programming concepts test and two tests to measure their CT. During the sessions, all students were taught according to MECOPROG. Finally, they took the three tests again. A significant increase in the results on all the tests has been measured, supporting the use of metaphors and Scratch to teach computer programming concepts to Primary Education students to develop their CT. •Computational Thinking can be improved using metaphors and Scratch.•Primary Education students' Computational Thinking can be improved.•Primary Education students can learn basic programming concepts.